Transient Behaviour of the Adsorption Heat Pump with the Multiple Adsorbent-Tube Type Adsorber - Hasatani, Masanobu; Ito, Mutsuhito; Watanabe, Fujio (KAGAKU KOGAKU RONBUNSHU, 1996)
The transient behaviour of an adsorption heat pump (AHP) with a multiple adsorbent-tube (MAT) type adsorber containing a silica gel module (ST-module), which was proposed to enhance heat transfer, has been simulated numerically in a cycle operation. Numerical results of heat and mass transfer accompanying the adsorption/desorption process of water vapour in the ST-module agreed with experimental ones. In addition, the time-changes of the amount adsorbed, temperature distributions in the MAT type adsorber, and periods of adsorption/desorption can be compositely explained by the isotherm and the adsorption/desorption rates. Also, form parametric studies on the performance of this AHP, it was found that the residual amount adsorbed at the end of the desorption process prevents effective generation of heat in the cycle operation of this AHP.